2014
DOI: 10.1080/10503307.2014.913322
|View full text |Cite
|
Sign up to set email alerts
|

Cultural adaptation in measuring common client characteristics with an urban Mainland Chinese sample

Abstract: This supported that regardless of whether one is in presumably different cultural contexts of the USA or China, psychological distress is expressed in a few basic channels of internalized distress, externalized distress, and interpersonal relations, from which different manifestations in different culture were also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Bijwaard and Wang (2016) reported that work stress has a bad physiological and psychological influence on a worker in an organization (or an institution) when individual capability cannot live up to the corresponding expectation. Milbourne and Wilkinson (2015) defined work stress as the spiritual fatigue caused by being slowly exposed to heavy work stress; when the person felt exhausted and emptied, such physical and mental exhaustion at work would result in the lack of work enthusiasm, high frustration, nervousness, and even insomnia, headache, anxiety, and depression (Song et al, 2015). Gullo et al (2015) divided stressors into interpersonal relationship stressors, task relationship stressors, organizational relationship stressors, and physical and mental relationship stressors.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Bijwaard and Wang (2016) reported that work stress has a bad physiological and psychological influence on a worker in an organization (or an institution) when individual capability cannot live up to the corresponding expectation. Milbourne and Wilkinson (2015) defined work stress as the spiritual fatigue caused by being slowly exposed to heavy work stress; when the person felt exhausted and emptied, such physical and mental exhaustion at work would result in the lack of work enthusiasm, high frustration, nervousness, and even insomnia, headache, anxiety, and depression (Song et al, 2015). Gullo et al (2015) divided stressors into interpersonal relationship stressors, task relationship stressors, organizational relationship stressors, and physical and mental relationship stressors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the beginning of expatriation, an individual may be anxious about the strange environment. Proper local guidance and necessary directions for work offered before the expatriation can be of great help for an expatriate (Song et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some cross‐cultural comparisons of patient reactance × therapist directiveness have been explored by research. While similarity to North American samples is the norm among South American and European studies (e.g., Beutler et al, ; Corbella et al, ), there are some indications of differences among Asian and non‐Asian populations (e.g., Beutler, ; Song et al, ). To date, the patterns related to reactance seem to transcend geographic and ethnic boundaries, but some distinctiveness appears also to be present among Asian groups.…”
Section: Diversity Considerationsmentioning
confidence: 99%
“…In the beginning of expatriation, an individual would be anxious about the strange environment. When proper local guidance and necessary directions for work were off ered before the expatriation, it would be a great help for an expatriate (Song et al, 2015). Accordingly, the following hypothesis is proposed in this study.…”
Section: Job Involvementmentioning
confidence: 95%
“…Bijwaard & Wang (2016) explained work stress as bad physiological and psychological infl uence on a worker in an organization (or an institution) when individual capability could not bear the correspondent expectation. Milbourne & Wilkinson (2015) defi ned work stress as the spiritual fatigue caused by being slowly exposed in heavy work stress; when the person felt exhausted and emptied, such physical and mental exhaustion at work would result in the lack of work enthusiasm, strong frustration, nervousness, and even insomnia, headache, anxiety, and depression (Song et al, 2015). Gullo et al (2015) divided stressors into interpersonal relationship stressor, task relationship stressor, organizational relationship stressor, and physical & mental relationship stressor.…”
Section: Work Stressmentioning
confidence: 99%